THE IMPORTANCE OF USING NATIVE LANGUAGE IN ENGLISH CLASSES - Toshmatova, Sitorabonu (Журнал иностранных языков и лингвистики, 2021)
ABSTRACT Present article shows that the usage of mother tongue in learning second foreign language classrooms has long been a controversy in the field of language teaching. Understanding the background of the controversy, this paper tries to review the treatment of a first language by leading language teaching methods. Then, the review is focused on the results of current research on whether the use of the first language hinders or assists second/foreign language acquisition. Key words: native language, learning strategy, language teaching method